The cyber effect : a pioneering cyberpsychologist explains how human behavior changes online - Aiken, Mary (Spiegel & Grau, 2016)
"From one of the world's leading experts in cyberpsychology--a discipline that combines psychology, forensics, and technology--comes a groundbreaking exploration of the impact of technology on human behavior. In the first book of its kind, Mary Aiken applies her expertise in cyber-behavioral analysis to a range of subjects, including criminal activity on the Deep Web and Darknet; deviant behavior; Internet addictions; the impact of technology on the developing child; teenagers and the Web; cyber-romance and cyber-friendships; cyberchondria; the future of artificial intelligence; and the positive effects on our digital selves, such as online altruism"--